Learning path based-portfolio for personalized learning - Romero, Lucila (2017)
Nowadays, lot of human activities have been affected by the use of technology needed to change in order to adapted. Particularly, in education domain the changes that occurred were not enough to break the traditional schemas of teaching. In this way, more and more people claim for real remodeling. Mainly, one of the most important subject is the necessity to adapt the teaching process to the particular characteristics of students, in a king of personalized learning. This work presents a conceptual framework, which proposes learning path based-portfolio as a way to personalize education. This framework uses semantic technologies, logical rules and agents to determine the student learning level and based on that propose course of actions.